1997
DOI: 10.1017/s0952523800011500
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate containing neurons in the cat superior colliculus revealed by immunocytochemistry

Abstract: Glutamate is the probable neurotransmitter of both retinal and cortical afferents to the cat superior colliculus (SC). The present study shows that glutamate is also contained in many postsynaptic neurons in SC. The distribution, morphology, and ultrastructure of neurons in SC were examined using glutamate antibody immunocytochemistry. Labeled cells were widely distributed throughout, but a specific laminar pattern was evident. Relatively few cells were found in the zonal and upper superficial gray layers (SGL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 29 publications
2
14
0
1
Order By: Relevance
“…GABA accumulation or GABA-like immunoreactivity have been shown for horizontal, piriform, and stellate cells, and all of these populations of morphologically defined cell types are likely to include local GABAergic interneurons (Mize et al, 1982;Mize, 1988Mize, , 1992. However, cells with stellate morphology can also show glutamate-like immunoreactivity, and therefore this morphological class may also include nonGABAergic projection neurons (Jeon et al, 1997). Narrow-field cells and wide-field cells are not GABAergic and are regarded as projection neurons.…”
Section: Correlation Of Responses To So Stimulation With Morphologicamentioning
confidence: 99%
“…GABA accumulation or GABA-like immunoreactivity have been shown for horizontal, piriform, and stellate cells, and all of these populations of morphologically defined cell types are likely to include local GABAergic interneurons (Mize et al, 1982;Mize, 1988Mize, , 1992. However, cells with stellate morphology can also show glutamate-like immunoreactivity, and therefore this morphological class may also include nonGABAergic projection neurons (Jeon et al, 1997). Narrow-field cells and wide-field cells are not GABAergic and are regarded as projection neurons.…”
Section: Correlation Of Responses To So Stimulation With Morphologicamentioning
confidence: 99%
“…1 A) (Mooney et al, 1985;Jeon et al, 1997). These neurons express L-type Ca 2ϩ channels in the mouse sSC and probably correspond to the vertical fusiform neurons thought to be glutamate-containing relay cells in the cat's SC (Jeon et al, 1997).…”
Section: Stimulation At 20 Hz For 20 S Induces Ltpmentioning
confidence: 92%
“…The selected neurons lie in the intermediate and deeper SGS and have radially elongated or pyramidal cell bodies with several apical and basal dendrites directed, respectively, toward the pia and the deeper collicular layers. These cells have been termed narrow-field vertical neurons by previous investigators (Langer and Lund, 1974) and have been shown to be excited by visual stimulation in rodents (Mooney et al, 1985) and to be glutamatergic in cats (Jeon et al, 1997). Neuronal soma and proximal dendrites were visualized using a Nikon (Tokyo, Japan; E600FN) infrared differential interference contrast (DIC) microscope with a 60ϫ water-immersion objective and video camera (CCD-300T-RC; DAGE MTI, Michigan City, IN) and filled with biocytin (see below) in 15-20 experiments to verify the relationship between the DIC images and the full extent of the dendritic arbor.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…Além disso, consideramos o fato que há perda da maquinaria protéica, como fatores de transcrição, das aferências retinianas e perda do aporte protéico nos terminais neuronais em degeneração no colículo superior. Por exemplo, remoção unilateral de áreas corticais visuais leva a redução de glutamato na neurópila e pericários no CS de gatos, provavelmente interferindo em processos neuroquímicos das células do CS (Jeon et al, 1997a;Jeon et al, 1997b).…”
Section: Discussionunclassified